Meningkatkan Hasil Belajar Bola Voli Mini Melalui Pendekatan Permainan Kelompok (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
This study is a mini volleyball How Learning through playgroup at the fourth-grade students of SD Negeri 01 Lumeneng District, Paninggaran Kab. Pekalongan Year 2014 While this research aims to enhance learning with the mini volleyball game modification group. Physical education is basically education through physical activity is used as a medium to achieve the overall development of the individual. Based on the analysis of the percentage of prasiklus with a percentage of 42.9% due to the complete breakdown of 9 children then headed to the first cycle increased with the percentage of 66.66% due to the breakdown of children and 14 children completed the second cycle to increase by 85.7% completion percentage with details 18 children completed, then by the study of indicators of successfully targeted 80% success.